Free surfactant synthesis of microcrystalline CdS by solvothermal reaction - Titipun Thongtem (2018)
Microcrystalline CdS was solvothermally synthesized by free surfactant reaction at 200 °C in a variety of solvents [benzene (BZ), toluene (TL), p-xylene (XL), cyclohexane (CHX) and tetrahydrofuran (THF)]. An X-ray diffractometer (XRD), a selected area electron diffraction (SAED) technique and an energy dispersive X-ray (EDX) analyzer show that the products are CdS (hexagonal structure) composed of Cd and S. The SAED patterns are also in accord with a simulation model. Strong fundamental and weak overtone modes were detected using a Raman spectrometer at 297.0 and 597.1 cm- 1, respectively. By using a transmission electron microscope (TEM), those synthesized in BZ, TL and XL are the mixtures of hexagonal and triangular plates. They are hexagonal and rod shapes in CHX and THF, respectively. Photoluminescent (PL) energies at the maximum intensities were detected over the range of 3.10-3.16 eV (392-400 nm). © 2006.